The relationship between data visualization and decision making: analysis and impact of visualization for better understanding of information - N.S. Prasol; D.V. Fyrikhata; A.Yu. Levchenko (Технічна інженерія)
In today's world, where volumes of data are constantly growing, visualization is a powerful tool for their analysis and interpretation. Effective visualization can help people better understand complex data, uncover hidden patterns and trends, and make more informed decisions. Visual tools, such as graphs, charts, maps, make data comprehensible to humans, compared to text tables and numerical series. Visualization allows us to quickly see changes over time that may not be obvious when analyzing textual data. This can help in predicting future events and making effective decisions. Through better understanding of data, visualization leads to improved outcomes in various fields such as business, science, medicine and government. Data visualization can help: doctors and nurses to better diagnose diseases, to monitor the condition of patients and to make treatment decisions; for companies to track sales, to analyze customer behavior, to optimize marketing campaigns, and to make better resource management decisions; researchers to discover new patterns in the data, to draw conclusions and to develop theories; governments to track economic performance, to analyze social trends and to make better policy decisions, etc.